Perlindungan Konsumen Atas Penyebaran Berita Bohong Melalui Transaksi Elektronik Yang Mengakibatkan Kerugian Konsumen - Elfrida Ratnawati; Faruqy Nailufar; Rosdiana Rosdiana (Jurnal de jure, 2023)
Guidelines for implementing consumer understanding in Article 28 paragraph (1) of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE) which provide boundaries and scope of application, which were originally very broad and in general becomes narrower and specific where the definition of consumer in Law Number 8 of 1999 concerning Consumer Protection is only specifically for Final Consumers as in the Joint Decree (SKB) of the Minister of Communication and Information, the Attorney General of the Republic of Indonesia and the Chief of Police Number 229 of 2021, Number 154 of 2021 and Number KB/2/VI/2021 which provides guidelines for implementing the definition of the word "consumer" namely in number 5 letter f which reads "The definition of a consumer in Article 28 paragraph (1) of the ITE Law refers to Law Number 8 of 1999 concerning Consumer Protection." . The purpose of this writing is to conduct a legal analysis related to how the protection of Intermediate Consumers is not regulated in Law Number 8 of 1999 concerning Consumer Protection in the application of Article 28 paragraph (1) of the ITE Law. The research method and approach in this paper is to use normative law which aims to study the law of development which is limited to the norms contained in the provisions of laws and regulations Keyword: End consumers; Intermediary Consumer, ITE